Pandemic-driven shift: increase in silver diamine fluoride utilization among Medicaid-enrolled children during the COVID-19 public health emergency - Meyer, Beau D.; Shoff, Carla; Chalmers, Natalia I. (Frontiers in Public Health, 2025)
IntroductionUntreated dental caries remains a significant public health issue, particularly among children and adolescents from low-income families, where disparities persist. The COVID-19 public health emergency (PHE) changed dental care practices, leading to an increased focus on minimally aerosolizing treatments such as silver diamine fluoride (SDF). This study aimed to describe the temporal changes in SDF utilization among Medicaid-enrolled children across the United States before and during the first half of the COVID-19 PHE. Additionally, the study examined the impact of demographics and state-level policies on SDF utilization.MethodsWe conducted a multiyear cross-sectional study using enrollment and claims data from the Transformed Medicaid Statistical Information System (T-MSIS) for 2019, 2020, and 2021. The study population included Medicaid and Children’s Health Insurance Program (CHIP) beneficiaries aged <21 years. We analyzed SDF utilization rates and compared them with other dental services, stratifying the data by age, sex, race/ethnicity, and rurality. Multilevel logistic regression models were used to identify significant predictors of SDF utilization.ResultsThe study included approximately 39 million children each year. SDF utilization per 1,000 enrollees increased from 9.10 in 2019 to 16.81 in 2021, with the most significant increases observed in children aged 0–6 years, those living in rural areas, and American Indian/Alaskan Native children. The state-level reimbursement policy for SDF was the most significant predictor, with children in states with such policies being 10.5 times more likely to receive SDF treatment.ConclusionThe COVID-19 PHE significantly impacted SDF utilization among Medicaid-enrolled children, highlighting the importance of state-level policies. The findings can be used to develop targeted approaches for clinicians to improve access to SDF treatment to address oral health disparities.